Comparison of The Performance of The Replacement Functions for Hard Disk Cache and Web Cache algorithms - سليمان, علي (Latakia University Journal -Engineering Sciences Series, 2020)
In this research paper, we compare the basic cache algorithms in terms of performance and speed for the purposes of web caching for dynamic content and hard disk buffering purposes, by studying the traditional algorithms in this field, in order to determine the utilization of the basic algorithms in disk storage in the field of web caching. The results shows that algorithms with replacement functions that rely on basic indicators (such as LRU, LFU) give better results in storage for storage purposes in hard drives, while web caching algorithms need additional benchmarks for replacement work to get high performance indicators, Web Cache algorithms also show lower performance then that hard drive, so the need to constantly develop the Web cache algorithm.